Supply Chain Management (SCM) utilisation based on SCM drivers in manufacturing industry - Jachan Matthew,; Norfaridatul Akmaliah Othman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Supply chain management (SCM) plays a significant role in enabling manufacturing industry to gain competitive advantage. However, very little attention has been paid to SCM utilisation in manufacturing industry. Therefore, the objective of the study is to explore the awareness of SCM among manufacturers, to determine SCM utilisation based on SCM drivers and to determine the relationship between SCM and competitive advantage. This study has focused on the management aspects of SCM, and provides a theoretical framework to understand a company's performance through SCM in achieving competitiveness. The research design which was based on the established and recommended procedures in literature was utilised to determine the nature of the methodology. A quantitative approach through questionnaire development was utilised. Data collection was distributed randomly to 200 respondents from the manufacturing industry in Malaysia. 150 completed questionnaires were returned and used to measure the relationship between SCM drivers and competitive advantage. The relationship between SCM and competitive advantage were tested and inventory, transportation, information technology, and pricing were found to be strongly related to the competitive advantage in the manufacturing industry; meanwhile, the results show that outsourcing and facility were not strongly related to the competitive advantage. The findings of this study have contributed both to the academic and pragmatic realms. This study adds to the literature on SCM. The results have been essential to measure the implications of SCM in the manufacturing industry.